The production and reproductive traits among different goat breeds in southwestern region of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2023)
In Bangladesh, a comprehensive study was conducted over one year to compare the reproductive and productive performance of Black Bengal, Jamunapari, and crossbred goats. The study involved a sample size of 226 goats and provided insightful information on the distinctive capabilities of each type of goat breeds. Most of the doe were 21–30 months of age, and their weight was 21–30 kg. The feed supply for the doe was concentrated green grass, whereas the kids got supplementary feed like rice bran. Among the reproductive traits, age at puberty, age of first kidding, and age of the first conception were significantly (P